Trumpocalypse restoring American democracy (New York, NY Harper, 2020)
"A huge swath of Americans see the rest of the country building a future that doesn't have a place for them. It's no wonder they'd rather burn it all down. But the fire can be stopped by Americans who act now to protect their country and its democracy"-- Provided by publisher.
Includes index
Keywords: Trump, Donald, 1946-